UPAYA PENINGKATAN PRESTASI BELAJAR IPS MELALUI COOPERATIVE LEARNINGPADA SISWA KELAS VIII DI SMP NEGERI 3 GAMPING SLEMAN YOGYAKARTA - Nadziroh Nadziroh (Universitas Muhammadiyah Mataram, 2014)
This study is intended to increase the student’s achievement and process to excute the social studies learning with Cooperative Learningapproach. This study is a Classroom Action Research(CAR) implemented to 8 th grade students in SMPN 3 Gamping Sleman as the object of study. This study contains three cycles, starts from planning, implementation, monitoring, reflecting and improving. The data were collected by using learning achievement test, observations, and interviews. The data from learning achievement tests were analyzed by using the descriptive quantitative technique. The data from observations and interviews were analyzed by using the descriptive qualitative technique on the basics of the results of the observation and reflection. Findings suggest that by the Cooperative Learningapproach implementation, the social studies can get its best result. The student’s score increases. It is proved by the average score in each examination. Atthe first cycle, the average score is 66.44; the second cycle is 67.41; and the third cycles is 77.67